Mind the gap: Measured and Calculated Osmolarity are Not Interchangeable in Diabetic Hyperglycemic Emergencies - Blank, Sebastiaan Paul; Blank, Ruth Miriam (Experimental and Clinical Endocrinology & Diabetes, 2023)
Introduction Small case series have reported that diabetic ketoacidosis is associated with an elevated osmolar gap, while no previous studies have assessed the accuracy of calculated osmolarity in the hyperosmolar hyperglycemic state. The aim of this study was to characterize the magnitude of the osmolar gap in these conditions and assess whether this changes over time.Methods In this retrospective cohort study, two publicly available intensive care datasets were used: Medical Information Mart of Intensive Care IV and the eICU Collaborative Research Database. We identified adult admissions with diabetic ketoacidosis and the hyperosmolar hyperglycemic state who had measured osmolality results available contemporaneously with sodium, urea and glucose values. Calculated osmolarity was derived using the formula 2Na + glucose + urea (all values in mmol/L).Results We identified 995 paired values for measured and calculated osmolarity from 547 admissions (321 diabetic ketoacidosis, 103 hyperosmolar hyperglycemic states and 123 mixed presentations). A wide variation in the osmolar gap was seen, including substantial elevations and low and negative values. There was a greater frequency of raised osmolar gaps at the start of the admission, which tends to normalize by around 12–24 h. Similar results were seen regardless of the admission diagnosis.Conclusions The osmolar gap varies widely in diabetic ketoacidosis and the hyperosmolar hyperglycemic state and may be highly elevated, especially at admission. Clinicians should be aware that measured and calculated osmolarity values are not interchangeable in this population. These findings should be confirmed in a prospective study.
Keywords: diabetic ketoacidosis; hyperglycemic hyperosmolar nonketotic coma; osmolarity; osmolar gap